Surakarta Contemporary Artspace - Noviyanto, Itok; , Suryaning Setyowati, ST. MT; , Ir. Indrawati, MT (2015)
Surakarta Contemporary Art Space is a place of creativity and art galleries to exhibit and sell the works of contemporary or modern of local artists Surakarta. The works in question is a form of visual art works of two-dimensional and three-dimensional that is capable of producing an inner experience, inspiration, imagination and so for those who see or enjoy. Surakarta city is a city of creative industries and has many local artists, especially for contemporary art. Today was a little presence of contemporary art galleries in the city of Surakarta. The presence of Art Space can be used as a place of creativity to publish works properly or exhibited to a broad audience so that the messages contained in these works can be conveyed to a broad audience. Surakarta was chosen to be the location founding Contemporary Art Space as Surakarta, Surakarta public awareness of the arts and creative industries as well as rapid development. This can be seen by the frequent art events held in Surakarta which aims to raise public awareness of creativity and Surakarta towards art and creative industries. The existence of an art space, in addition to the exposition site works of art that have economic access, and symbolic dimension, is expected to be an oasis convergence of multiple perspectives for dialogue. Keywords: Gallery, Art, Contemporary, Visual, Creativity, and Artists